Fracture Healing and the Underexposed Role of Extracellular Vesicle-Based Cross Talk. Issue 5 (May 2018) - Qiao, Zhi; Greven, Johannes; Horst, Klemens; Pfeifer, Roman; Kobbe, Philipp; Pape, Hans-Christoph; Hildebrand, Frank
Abstract : ABSTRACT: The process of fracture healing is complex and requires an interaction of multiple organ systems. Cell–cell communication is known to be very important during this process. Extracellular vesicles (EVs) are small membranous vesicles generated from a variety of cells. Proteins, RNAs, small molecules, and mitochondria DNA were found to be transported among cells through EVs. EV-based cross talk represents a substantial cell–cell communication pattern that can both interact with cells through molecular surfaces and transfer molecules to cells. These interactions can assist in the synchronization of cellular functions among cells of the same kind, and coordinate the functions of different types of cells. After activation, platelets, neutrophils, macrophages, osteoblasts, osteoclasts, and mesenchymal stem cell (') all secrete EVs, promoting the fracture healing process. Moreover, some studies have found evidence that EVs may be used for diagnosis and treatment of delayed fracture healing, and may be significantly involved in the pathophysiology of fracture healing disturbances. In this review, we summarize recent findings on EVs released by fracture healing-related cells, and EV-mediated communications during fracture healing. We also highlight the potential applications of EVs in fracture healing. Lastly, the prospect of EVs for research and clinical use is discussed.